2012
DOI: 10.1016/j.pharmthera.2012.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Mirtazapine, and mirtazapine-like compounds as possible pharmacotherapy for substance abuse disorders: Evidence from the bench and the bedside

Abstract: Understanding substance use disorders (SUDs) and the problems associated with abstinence has grown in recent years. Nonetheless, highly efficacious treatment targeting relapse prevention has remained elusive, and there remains no FDA-approved pharmacotherapy for psychostimulant dependence. Preclinical and clinical investigations assessing the utility of classical antidepressants, which block monoamine reuptake, show mixed and often contradictory results. Mirtazapine (Remeron®) is a unique FDA-approved antidepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 117 publications
(178 reference statements)
3
21
0
Order By: Relevance
“…5, chronic mirtazapine infusion did not alter the improvements in akinesia provided by PPX; however, PPX-enhanced risk-taking was attenuated (albeit, modestly). This trend is in keeping with the ability of mirtazapine to reduce motivated behaviors sustained by abused drugs in rats and humans [1822,24,45] and ICSS-mediated decision-making in rats [46]. Outcomes also indicate that the systems engaged by mirtazapine may be more relevant to ICD than motor function.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…5, chronic mirtazapine infusion did not alter the improvements in akinesia provided by PPX; however, PPX-enhanced risk-taking was attenuated (albeit, modestly). This trend is in keeping with the ability of mirtazapine to reduce motivated behaviors sustained by abused drugs in rats and humans [1822,24,45] and ICSS-mediated decision-making in rats [46]. Outcomes also indicate that the systems engaged by mirtazapine may be more relevant to ICD than motor function.…”
Section: Discussionsupporting
confidence: 59%
“…Thus, we postulated that therapies which hold promise for addiction may provide relief from ICDs. Mirtazapine, an atypical antidepressant, reduces behaviors associated with substance use disorders in rats [1822] and humans [23,24]. Moreover, mirtazapine has been used to treat anxiety, depression, and psychosis in PD patients, and is well-tolerated by PD patients on dopamine agonist therapy with little to no effect on the motor benefits afforded by the agonist [2530].…”
Section: Introductionmentioning
confidence: 99%
“…Mirtazapine is an atypical antidepressant with a complex pharmacological profile that includes antagonism at 5-HT 2A/2C receptors (De Boer, 1995;Wikstrom et al, 2002). Mirtazapine attenuates various behaviors motivated by abused drugs, including methamphetamine (Herrold et al, 2009;Voigt et al, 2011;Graves and Napier, 2011;Voigt and Napier, 2011) and morphine (Graves et al, 2012a) in rats, and reduces cocaine intake in humans (Graves et al, 2012b). We recently revealed that mirtazapine reduces the capacity of the dopamine D2/D3 receptor agonist, pramipexole, to induce risky decision-making by rats performing a probability discounting task (Holtz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Findings from preclinical studies involving rats and published case studies in humans suggest that mirtazapine therapy may contribute to successful outcomes across a number of substance use disorders, including alcohol use disorders, amphetamine dependence, and other substance use disorders [11,12]. Consequently, those recent reviews have suggested that preliminary findings suggest a promising role for mirtazapine in addiction pharmacotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, those recent reviews have suggested that preliminary findings suggest a promising role for mirtazapine in addiction pharmacotherapy. However, a large scale clinical trial assessing the utility of mirtazapine in the treatment of substance use disorders has not yet been conducted [12]. …”
Section: Introductionmentioning
confidence: 99%